Efektivitas Penerimaan Retribusi Parkir di Dinas Perhubungan Kabupaten Sumedang - Ibnu Abdul Basith; Asep Hidayat; Dedeng Yusuf Maolani (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Effectiveness is a measure of the success or failure of achieving organizational goals. If the organization succeeds in achieving its goals, then the organization can be said to have been effective. Levies are payments from the people to the government, in which there is a remuneration relationship that is directly received by the payment of levies. This study aims to determine how effective the acceptance of parking levy from the Sumedang Regency Transportation Service is during the last five years, from 2016 to 2020 by looking at the dimensions of effectiveness according to Duncan, namely goal achievement, integration and adaptation. This study uses a descriptive method with a qualitative approach. In this study, two sources of data were used, namely primary and secondary data sources. The data collection techniques are interview and documentation techniques. The sample selection technique used is purposive sampling and for data analysis, the researcher uses Miles and Huberman's model theory. The results showed that since 2016-2020 parking levy receipts were still classified as ineffective. This is based on the dimensions of achieving the goal of parking levy income which still focuses on collecting retribution on the edge of public roads, while incidental parking from community activities that should have been deposited has not been maximized. In the dimension of integration , although other government agencies have assisted in controlling, there are still many parties outside the existing system in the field also influence the income that should be deposited by the parking attendant to the Sumedang Regency Transportation Service officer, resulting in a lot of revenue leakage. From the adaptation dimension, the Sumedang Regency Transportation Service during 2016 to 2020 did not have many changes regarding the collection of parking fees.Keywords: Effectiveness, parking levy, local revenue